2011
DOI: 10.1016/j.ajpath.2011.02.043
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1 Involvement in Inflammatory Tissue Fibrosis in Mice

Abstract: We examined whether absence or blocking of transient receptor potential vanilloid subtype 1 (TRPV1) affects the level of inflammation and fibrosis/scarring during healing of injured tissue using an alkali burn model of cornea in mice. A cornea burn was produced with 1 N NaOH instilled into one eye of TRPV1-/- (KO) (n = 88) or TRPV1+/+ (n = 94) mice. Examinations of the corneal surface and eye globe size suggested that the loss of TRPV1 suppressed inflammation and fibrosis/scarring after alkali burn, and this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 84 publications
(101 citation statements)
references
References 38 publications
7
89
0
5
Order By: Relevance
“…Cellular constituent release caused by a severe chemical injury also induces TRPV1 activation, followed by corneal opacification and chronic dysregulated inflammation during wound healing. 27,28,31,32 As increases in cell proliferation in cancer are associated with rises in functional TRPV1 expression and activity, 33,34 we hypothesized that this change is associated with conjunctival hyperplasia in pterygium.…”
Section: Methodsmentioning
confidence: 99%
“…Cellular constituent release caused by a severe chemical injury also induces TRPV1 activation, followed by corneal opacification and chronic dysregulated inflammation during wound healing. 27,28,31,32 As increases in cell proliferation in cancer are associated with rises in functional TRPV1 expression and activity, 33,34 we hypothesized that this change is associated with conjunctival hyperplasia in pterygium.…”
Section: Methodsmentioning
confidence: 99%
“…Members of the transient receptor potential (TRP) channel superfamily, which include subfamilies in corneal epithelial and keratocytes, respond to environmental irritants inducing afferent impulses to the central nervous system (79) . Chemical burns in mice induce a specific TRP vanilloid type 1 (TRPV1) channel deregulated inflammatory responses leading to corneal melt and opacification (80) . The injury-induced inflammatory and opacification responses resulting from TRPV1 activation were attributed to the up regulation of pro inflammatory and chemo attractive cytokines.…”
mentioning
confidence: 99%
“…In accordance, Okada et al [17] added that the involvement of inflammatory cells and disorganization of collagen fibers in the wound healing process of an alkali-burned cornea leads to further release of fibrogenic cytokines that augment the tissue inflammation and subsequent corneal scarring. Also this was in agreement with Torricelli et al [16] who stated that highly disorganized extracellular matrix was observed in corneas with haze.…”
Section: Discussionmentioning
confidence: 76%